Echocardiographic Biatrial Remodelling and Diastolic Function Assessment in Long-Term Follow-Up after Typical Atrial Flutter Ablation - Pilar Cabanas-Grandío; Javier García-Seara; Francisco Gude; José Luis Martínez-Sande; Xesús Alberte Fernández-López; Felipe Bisbal; Emad Abu-Assi; José Ramón González-Juanatey (Journal of Cardiovascular Medicine and Cardiology - Peertechz Publications, 2014)
Background: A reverse left atrial (LA) remodelling after atrial fibrillation (AF) ablation has been reported and a relationship between diastolic function and AF is well known. However, there is little information about atrial remodelling and diastolic function after cavotricuspid isthmus (CTI) ablation. We aimed to evaluate long-term biatrial remodelling and diastolic function in patients undergoing CTI ablation. Methods: A transthoracic echocardiography was performed at baseline and at longterm follow-up (6.3 ± 0.5 years) in a total of 39 patients who underwent AFl ablation. Right atrial end diastolic areas (RAEDA) and end systolic areas (RAESA), right atrial contraction fraction (RACF), mitral A wave velocity, E/A rate and LA diameter were measured. They were compared using the Wilcoxon rank sum test. Results: Mean (SD) age was 64 (10) years, 82% male, 49% hypertension and 44% prior AF episodes. Basal RAEDA and RAESA were higher than at follow-up: median (IQR) of 24.6 cm² (19.8-28.2) vs. 20.0 cm² (16.0-25.0), p = 0.017 and 17.4 cm² (13.0-19.3) vs. 12.0 cm² (9.8-17.0), p = 0.001, respectively. RACF was higher at follow-up: 0.41 (0.35- 0.45) vs. 0.31 (0.19-0.37), p = 0.001. Basal mitral A wave velocity was lower than at follow-up: 0.51 (0.4-0.6) vs. 0.78 (0.7-0.9), p =0.001 and E/A rate was higher 1.9 (1.2-3.1) vs. 0.9 (0.7-1.1), p = 0.001. LA diameter at baseline was 44.8 mm (39.3-50.7) vs. 46 mm (41.5-51.5) at follow-up, p <0.001. Conclusion: AFl ablation led to reverse remodelling of the right atrium and improved diastolic dysfunction parameters in the long-term follow-up.